Numerical and experimental study of a novel valve using the return stream energy to adjust the speed of a hydraulic actuator - Filo, Grzegorz (Strojniški vestnik, 2019)
This article discusses the possibility of increasing the speed of movement of a single-sided hydraulic cylinder piston rod using a fluid stream from the return line. Directing the return stream back to the supply line instead of the fluid reservoir causes significant increase in the inflow rate to the actuator. This situation may arise when the piston rod of the cylinder is not fully loaded on part of the movement range. As part of this work, we proposed a solution in the form of a novel control valve, consisting of a throttle valve and a differential valve controlled by the pressure difference between the supply line and the return line. A geometric model was created using SolidWorks, then a simulation model was made in Matlab/Simulink. Next, simulations were carried out to prove that the use of the return fluid stream gives a possibility of a significant increase in the piston rod speed. The results of the numerical analyses were verified on a test bench where the valve prototype was tested. Speed characteristics of the piston rod against both payload force and throttle valve setting were determined. High convergence with the simulation results was obtained. It has also been confirmed that the proposed solution can be advantageous in practical applications.
Keywords: hydraulic actuator speed adjustment; hydraulic system modelling; modeliranje hidravličnih sistemov; nova konstrukcija regulacijskega ventila; novel control valve design; raba energije povratnega toka; return stream energy usage; uravnavanje hitrosti hidravličnega aktuatorja